The Effect of Using Comics on the Vocabulary Achievement of Junior High School Students - Nur Aisyah Imroatul Hasanah (Fakultas Keguruan dan Ilmu Pendidikan, 2024)
Vocabulary can be regarded as the first thing to be learned when learning English, as it serves as the foundation for all other English skills (Khafidhoh & Carolina, 2019). Students require an understanding of vocabulary in order to comprehend the language. Having insufficient vocabulary will undoubtedly make students have difficulties when engaging in speaking, writing, listening, and reading activities (Sari et al., 2021). The issue of insufficient vocabulary in junior high school students was addressed in some studies. One of them, conducted by the Educational Testing Service in 2017, revealed that nearly 50% of high school graduates lacked the necessary vocabulary skills to succeed in college-level coursework. This implied that the problem might start much earlier at junior high schools. The problem of students‟ insufficient vocabulary may be caused by various reasons, including students‟ lack of familiarity with the vocabulary, their limited exposure to English language, and can also be attributed to the monotonous teaching methods or the teaching media used by the teachers (Azizzah & Hamid, 2022). Especially since students still need a teacher figure to help them learning a new language, teachers frequently have to aid students in discovering and interpreting the new vocabulary they have learned. It is crucial for teachers to facilitate students‟ comprehension of a new vocabulary and the overall meaning of a sentence. Consequently, when students encounter new words with which they are unfamiliar, teachers can teach the words in question by making use of media to help students remember the words better. One of the media that the teacher can use is comics. This is due to the fact that comics can act as media that give students room for imagination, encourage them with their creative way of thinking. Using comics as media in vocabulary teaching and learning has been suggested as an effective approach within the students‟ learning process (Wijaya et al., 2021).